Solvent effects on chemical processes: New solvents designed on the basis of the molecular-microscopic properties of (molecular solvent + 1,3-dialkylimidazolium) binary mixtures - Mancini, Pedro Maximo Emilio (2008)
The purpose of this work was to analyze the microscopic feature of binary solvent systems formed by a molecular solvent (acetonitrile or dimethylformamide or methanol) and an ionic liquid (IL) cosolvent [1-(1-butyl)-3- methylimidazolium tetrafluoroborate or 1-(1-butyl)-3-methylimidazolium hexafluorophosphate]. The empirical solvatochromic solvent parameters E T(30), π*, α, and β were determined from the solvatochromic shifts of adequate indicators. The behavior of the solvent systems was analyzed according to their deviation from ideality. The study focused on the identification of solvent mixtures with relevant solvating properties in order to select mixed solvents with particular characteristics. The comparison of the molecular-microscopic solvent parameters corresponding to the selected binary mixtures with both ILs considered at similar mixed-solvent composition revealed that the difference is centered on the basic character of them. A kinetic study of a nucleophilic aromatic substitution reaction between 1-fluoro-2,4-dinitrobenzene (FDNB) and 1-butylamine (BU) developed in (acetonitrile or dimethylformamide + IL) solvent mixtures is presented in order to investigate and compare the solvent effects on a chemical process. For the explored reactive systems the solvation behavior is dominated by both the dipolarity/polarizability and the basicity of the media, contributing these solvent properties to accelerating the chemical process.